NORMALIZATION - Dr. Cherif SAIB (MOHAMED Boudiaf University of M’sila, 2025)
he handout of the norms (Normalization- de jure standards)- discusses : Definitions of standards and general information on the importance of standardization are dealt with in the first chapter. The difference between standards and other industrial documents are part of the second chapter. A little bit of the history of legitimate international standard-setting entities will be part of the third chapter. When in the fourth chapter we discuss the steps to develop a standard and the entities that take care of its characteristics The development and progress of the ISO standards is been established in the fifth chapter In the sixth and the seventh chapters highlighted the norms equivalencies and international classes of norms. The patent and industrial and intellectual property will be fully explained in the eighth chapter. In chapter nine the regulation and normalization are discussed, The certification and accredition are well explained in chapter ten, The eleventh chapter discusses the manufacturing standards, We end with a bibliography of the references used for the establishment of this course handout.
Third year Bachelor in Materials Engineering (3eme Année Licence Génie Des Matériaux)
Keywords: Normalization- industrial documents- ISO standards- patent and industrial and intellectual property -the regulation- certification and accredition - manufacturing standards.